The use of functional appliances for class II malocclusions: a nation-wide cross-sectional survey of orthodontists in Australia - Hastie Thomas; Goonewardene Mithran; Lee Richard; Naoum Steven; Razza Mike (Australasian Orthodontic Journal)
If detected at the appropriate age, a Class II malocclusion can be improved or camouflaged by utilising functional appliances to manipulate a child’s skeletal growth spurt to advantage.